ANALISIS KELAYAKAN TINGKAT KEBISINGAN DAN INTENSITAS PENCAHAYAAN RUANG PERPUSTAKAAN SEKOLAH DASAR DI KOTA MALANG MENGGUNAKAN SOUND LEVEL METER DAN LUX METER - Dieksa Saputri Himawan; Nur Latifah Khomsiati; Immanuel Surya Pratama; Fadilatul Anisa; Tee Tze Kiong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The library is one of the key facilities in the student learning process that requires an adequate physical environment, particularly regarding noise levels and lighting intensity. This study aims to analyze the suitability of noise levels and lighting intensity in the library of an elementary school in Malang City based on applicable quality standards. Measurements were taken at 30 observation points at 20-minute intervals, from 10:00 AM to 12:00 PM, using a sound level meter and a lux meter. The reference standards used were SNI 03-6386-2000 for noise levels (≤55 dBA for reading rooms) and SNI 03-6197-2000 for lighting intensity (≥300 lux for library reading rooms). The analysis results showed that most measurement points did not meet the minimum lighting standards, while most noise levels exceeded the permissible thresholds. This study provides recommendations for improvement, including the addition of artificial light sources and the use of sound-absorbing materials to enhance the comfort of the library reading room.